1997
DOI: 10.1149/1.1837531
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Exchange and Diffusion Coefficients of Strontium‐Doped Lanthanum Ferrites by Electrical Conductivity Relaxation

Abstract: Electrical conductivity relaxation experiments were performed on thin specimens of Lai_rSrFe0a_, (x =0.1, 0.4) at oxygen partial pressures Po, = 10 -1 bar in the temperature range 923 to 1223 K. The transient response of the electrical conductivity after a sudden change of the ambient oxygen partial pressure was analyzed in the frequency domain. The latter procedure allowed diffusion-limited and surface exchange-limited kinetics of re-equilibration to be distinguished. The response of specimens with thiçknesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
202
3
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(230 citation statements)
references
References 6 publications
15
202
3
3
Order By: Relevance
“…Previous studies reported that values of k ex for LSC are 1-2 orders of magnitude higher than k ex for LSF. [27][28][29][30] However, these reported experimental results were measured using depth profiling or conductivity relaxation methods, which lack the surface sensitivity that the surface exchange technique that is reported here can provide. The surface exchange process measured with these methods is measured either under the diffusion-limited regime of the exchange process, or under the mixed diffusion-surface regime, due to the use of sample thickness.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that values of k ex for LSC are 1-2 orders of magnitude higher than k ex for LSF. [27][28][29][30] However, these reported experimental results were measured using depth profiling or conductivity relaxation methods, which lack the surface sensitivity that the surface exchange technique that is reported here can provide. The surface exchange process measured with these methods is measured either under the diffusion-limited regime of the exchange process, or under the mixed diffusion-surface regime, due to the use of sample thickness.…”
Section: Resultsmentioning
confidence: 99%
“…Surface exchange and bulk diffusion coefficients obtained from ECR measurements have been shown to exhibit a discrepancy between steps performed from high to low (reduction) and low to high (oxidation) oxygen partial pressures in a number of reports [3,4,5,6,7]. The apparent difference in oxidation and reduction values is in general more pronounced at decreasing p O 2 .…”
Section: Motivation and Initial Resultsmentioning
confidence: 99%
“…By performing a step change in oxygen partial pressure, which will lead to a change in the oxygen non-stoichiometry, and monitoring the electronic conductivity response, the change in non-stoichiometry over time and thus the oxygen transport kinetics can be deduced. The validity of this technique, especially for materials exhibiting high oxygen exchange rates and/or at low partial pressures of oxygen, has however been questioned [3,4]. In this study we will investigate the validity of ECR in terms of transport coefficient assessment both from an experimental and a theoretical modelling approach.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Several studies were performed on the defect chemistry and transport properties of LSF [21][22][23][24][25][26][27][28][29][30][31] [2] Fe 4+ states can be interpreted as electron holes (h • ) and those determine the electronic conductivity at high oxygen partial pressure as they are the majority mobile charge carrier. [20][21][22] Towards lower oxygen partial pressures (and/or higher temperatures) the equilibrium of Eq.…”
mentioning
confidence: 99%